1980
DOI: 10.1111/j.0033-0124.1980.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Accessibility to Employment in an Urban Area: Milwaukee, 1927–1963

Abstract: Data from transportation studies are used to examine changes in accessibility to employment opportunities in the Milwaukee urban area from 1927 to 1963. Low‐status areas of the city tended to experience the greatest decreases in employment accessibility compared with other parts of the urban area. Furthermore, increasing levels of employment accessibility were associated with greater amounts of new housing, whereas decreases in housing vacancies and population occured in areas with declining accessibility to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The quantity $Ad#) is the measure of the accessibility of libraryj to the population in census tract i. It is the factor determining the interaction of census tract i with library j and the proportion of the total library circulation from census tract i that goes to library j (Ottensmann, 1980). Thus, for any census tract i, the total accessibility to the library services provided by all the libraries will be the sum overj, giving…”
Section: Accessibility and Distance-service Tradeoffsmentioning
confidence: 99%
“…The quantity $Ad#) is the measure of the accessibility of libraryj to the population in census tract i. It is the factor determining the interaction of census tract i with library j and the proportion of the total library circulation from census tract i that goes to library j (Ottensmann, 1980). Thus, for any census tract i, the total accessibility to the library services provided by all the libraries will be the sum overj, giving…”
Section: Accessibility and Distance-service Tradeoffsmentioning
confidence: 99%
“…Consumers shopping in neighborhoods with high percentages of black or elderly residents have been shown to pay more for groceries while shopping in dirtier stores with a more restricted selection of foodstuffs than those available to consumers shopping in other areas of town (Hall 1983). Additionally, studies have found that accessibility to landscapes offering a variety of amenities-such as parks, employment, or public transportation-is frequently wanting in inner-city neighborhoods (e.g., Ottensmann 1980;McLafferty 1982;Talen 1997;Holloway 1998b).…”
Section: Introductionmentioning
confidence: 99%